2007
DOI: 10.1097/rct.0b013e3180500d23
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pulmonary Lobe Variations Using Multidetector Row Computed Tomography

Abstract: The incidence of incomplete lobulation observed by multidetector CT in this study is remarkably lower than that reported in previous CT studies but is comparable with that reported from autopsy results. It is important to perform multidirectional observation using MPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 6 publications
2
15
2
Order By: Relevance
“…As a result, more than 90% of the patients involved in this study had incomplete fissures. This number is similar to the result (i.e., 95% of subjects have incomplete fissures) reported by Mahmut et al [18]. Typically, the oblique fissures, no matter in the right or the left lung, have an integrity level larger than 60%.…”
Section: Discussionsupporting
confidence: 91%
“…As a result, more than 90% of the patients involved in this study had incomplete fissures. This number is similar to the result (i.e., 95% of subjects have incomplete fissures) reported by Mahmut et al [18]. Typically, the oblique fissures, no matter in the right or the left lung, have an integrity level larger than 60%.…”
Section: Discussionsupporting
confidence: 91%
“…However, in this study, 9.1% of HFs were found to be discontinuous in the intermediate region, which might relate to the direction of HFs. In previous studies, among the four types of incomplete interlobar fissures, both ROFs and LOFs were most frequently observed as type 1, whereas HFs were most frequently observed as type 3 or type 4 (4,8). In this study, the results for ROFs and LOFs indicated agreement with these studies, but the results for HFs were different, as similar probabilities were observed for HFs of types 1, 3, and 4.…”
Section: Discussionsupporting
confidence: 87%
“…Based on several studies using high resolution CT (1.5 mm thick section) and thin-section CT (1-2 mm thick sections), the probability of having incomplete fissures can vary as 17.4%-87% for ROFs, 20.4%-86.9% for HFs, and 18.6%-70.4% for LOFs (4,6,8,(11)(12)(13). In this study, incomplete ROFs, HFs, and LOFs exhibited frequencies of 41.3%, 58.2%, and 45.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] The existence of incomplete fissures may reduce barriers that prevent the spread of diseases, such as pneumonia, and could also affect the distribution pattern of pleural effusion. Air leaks after lobectomies represent but one type of complication in lung cancer patients with incomplete fissures.…”
Section: Introductionmentioning
confidence: 99%